Structural phase transition in two-dimensional tetramer-cuprate Na₅RbCu₄(AsO₄)₄Cl₂ - Gnezdilov, V.; Bedarev, V.; Pashkevich, Yu.; Lemmens, P.; Zvyagin, S.; Gnatchenko, S.; Pashchenko, M.; Mo, X.; Queen, W.; Hwu, S.J. (Физика низких температур, 2007)
Using Raman scattering and optical birefringence we have investigated a low-temperature phase transition in single crystal of the two-dimensional Na₅RbCu₄(AsO₄)₄Cl₂. Phonon anomalies point to a first order nature of the transition. The observed transition is most probably related to a order-disorder transition of the Rb ion positions along the z axis within the ionic framework of mixed alkali metal chloride lattices.